2017
DOI: 10.1016/j.orgel.2017.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared electroluminescence from Nd(TTA) 3 phen in solution-processed small molecule organic light-emitting diodes

Abstract: International audienceWe report on the near infrared electroluminescence properties of a Nd3+ complex with thenoyltrifluoroacetone and 1,10-phenantroline ligands in solution-processed organic light-emitting diodes. Spin-coated blends containing a 1,3-bis(9-carbazolyl)benzene host doped with the Nd3+ complex were found to exhibit a photoluminescence quantum yield of about 0.5%, regardless of the doping concentration level. Electroluminescent devices based on these small molecule blends showed the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
5
22
0
Order By: Relevance
“…In 2017, Shahalizad and co‐workers employed Nd‐6 (Scheme ) to fabricate OLEDs by the solution‐processing method. A small molecule mCP with high triplet energy level of 2.9 eV was used as the host to ensure efficient energy transfer.…”
Section: Nir Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…In 2017, Shahalizad and co‐workers employed Nd‐6 (Scheme ) to fabricate OLEDs by the solution‐processing method. A small molecule mCP with high triplet energy level of 2.9 eV was used as the host to ensure efficient energy transfer.…”
Section: Nir Light Emission Lanthanide Complexesmentioning
confidence: 99%
“…However, very few organic materials emit in this spectral range and the ones that do typically suffer from poor emission efficiency. [5] Previous work focused on either small molecules, [6][7][8][9] polymers, [10] polymer nanocrystals [11] or solution processed quantum dots [12] . While these approaches certainly hold promise, important challenges remain.…”
mentioning
confidence: 99%
“…The electrical performance shown by device 3 is comparable with that of other efficient Nd-complex based devices. [24][25][26][27][28][29]31 Moreover, the irradiance shown by device 3 was observed at a lower voltage as compared to the reported ones, [24][25][26][27][28][29]31 which indicates that device 3 is ] (3). The single crystal X-ray analysis showed that complex 1 is nona-coordinated while complexes 2 and are octacoordinated, and they possess distorted square antiprismatic (D 4d ) and monocapped square antiprism (C 4v ) geometries, respectively.…”
Section: Nir-oleds Based On Nd Complexesmentioning
confidence: 94%
“…28 In 2019, a Nd complex, [Nd(tta) 3 (phen)], based device was reported with an EQE of 0.034% (tta = thenoyl trifluoroacetone and phen = 1,10-phenanthroline). 29 Considering the performances of the above mentioned devices, more efficient devices are still needed to be designed and fabricated to meet the requirements of practical applications.…”
Section: Introductionmentioning
confidence: 99%